SDS-PAGE protein profile of albumin extracted by steaming from four marine and three brackish-water fishes - NUR FATMA; METUSALACH METUSALACH; NURPUDJI ASTUTI TASLIM; MALA NURILMALA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fatma N, Metusalach, Taslim NA, Nurilmala M. 2023. SDS-PAGE protein profile of albumin extracted by steaming from four marine and three brackish-water fishes. Biodiversitas 24: 4027-4033. Snakehead fish is a type of fish that has been known as the best source of fish albumin. However, the increasing demand for and exploitation of snakehead fish albumin is not accompanied by the availability of sustainable snakehead fish stocks. Snakehead fish stocks in nature continue to experience depletion and cultivation efforts that have been carried out so far have not yielded satisfactory results. For this reason, it is necessary to find alternative sources of fish albumin. The purpose of this study was to determine the molecular weight of the albumin proteins extracted by water bath steaming from four marine fishes (Indian scad Decapterus russelli, short-bodied mackerel Rastrelliger brachysoma, goldband fusilier Pterocaesio chrysozona, Japanese threadfin bream Nemipterus japonicus) and three brackish-water fishes (white-lipped eel catfish Paraplotosus albilabris, barramundi Lates calcarifer, milkfish Chanos chanos). The method used was Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (SDS-PAGE) electrophoresis. Each sample was steamed in a water bath at 50°C for 30 minutes to obtain the crude extract's optimal yield and albumin content. The molecular weights of each protein band were analyzed using the Photocapt application, visualized and tabulated, and analyzed descriptively. Indian scad had six protein bands with three major (48 kD, 37 kD, 32 kD) and three minor bands (66 kD, 25 kD, 15 kD). Shortbodied mackerel had one major protein band (26 kD). Goldband fusilier had one major (33 kD) and four minor bands (50 kD, 69 kD, 57 kD, 26 kD). Japanese threadfin bream had one major (62 kD) and three minor bands (171 kD, 72 kD, 26 kD). White-lipped eel catfish had two major (41 kD, 34 kD and two minor bands (70 kD, 26 kD). Barramundi had one major (26 kD) and two minor bands (171 kD, 87 kD). Milkfish had one major (41 kD) and four minor bands (333 kD, 135 kD, 31 kD, 25 kD). It is hoped that this research will provide information on which fish have the potential as a source of fish albumin in terms of protein composition which resembles snakehead fish so that the properties provided are as good as albumin from snakehead fish.